Impact of donor hypertension on graft survival and function in living and deceased donor kidney transplantation: a nationwide prospective cohort study. Issue 11 (23rd November 2022) - Lee, Yu Ho; Kim, Jin Sug; Song, Sang Heon; Song, Seung Hwan; Shin, Ho Sik; Yang, Jaeseok; Ahn, Curie; Jeong, Kyung Hwan; Hwang, Hyeon Seok
Abstract : Objectives: Hypertensive living donors are potential candidates to expand the kidney donor pool. However, the impact of donor hypertension on graft survival and function remains to be clarified. Methods: We analyzed 3907 kidney transplant recipients registered in a nationwide prospective cohort from 2014 to 2018. Patients were divided by donor types and the presence of donor hypertension. The primary and secondary outcome was the occurrence of death-censored graft failure and renal allograft function, respectively. Results: The prevalence of hypertension was 9.4% (258/2740) and 19.9% (232/1167) in living and deceased donors, respectively. During a median follow-up of 21.8 months, death-censored graft survival rate was significantly worse in recipients of hypertensive living donors than in those of normotensive living donors ( P  = 0.008). In multivariable analysis, recipients of hypertensive living donors had a significantly increased risk of graft loss (adjusted hazard ratio 2.91; P  = 0.009). The risk of allograft loss was not different between recipients of hypertensive living and normotensive deceased donors. Propensity score-matched analyses had consistent worse graft survival rate in recipients of hypertensive living donors compared to those of normotensive living donors ( P  = 0.027), while it was not different between recipients of hypertensive living and normotensive deceased donors. Hypertension in living donors had a significant negative impact on one-year graft function (adjusted unstandardized β −3.64; P  = 0.011). Conclusions: Hypertensive living donor recipients have significantly higher risks of renal allograft loss than normotensive living donor recipients, and showed similar outcomes compared to recipients of normotensive deceased donors.